Exploring the Use of Flipped Classroom in Influencing Listening Comprehension of Civil Engineering Students - Juvrianto Chrissunday Jakob (IJET (Indonesian Journal of English Teaching), 2023)
Nowadays, maintaining students’ listening ability, particularly during this COVID-19 pandemic is difficult to do. One of the influential aspects in learning English which is also affected by learning patterns in today's pandemic era is listening comprehension. This study elaborates the influence of using flipped classroom to the learning motivation of civil engineering students of Politeknik Negeri Ambon. This study aims at finding out whether or not the use of flipped classroom influences students’ listening comprehension in learning English. The study applied quasi experimental design. The population of the study took two classes of the first semester of TKJJ Study Program in Civil Engineering Department of Politeknik Negeri Ambon as sample through cluster random sampling. One class act as experimental group and other class act as control group. Experimental group taught by implementing flipped classroom while control group taught by using traditional method. The teaching materials used in this study refers to English for Specific Purposes (ESP) namely English for Civil Engineering. The results of the study revealed that the use of flipped classroom encourage students’ listening comprehension as shown from data that t-test value (4.3) was higher than t-table value (2.000). It means that flipped classroom has influenced and improved students’ listening comprehension in classroom. Keywords: civil engineering, ESP, flipped classroom, listening